The Oxford handbook of personnel psychology - Cartwright, Susan, 1951-; Cooper, Cary L. (Oxford : Oxford University Press, 2008)
'The Oxford Handbook of Personnel Psychology' brings together contributions from leading international scholars within the field. The book is divided into six sections: Individual difference and work performance; Personnel selection Methodological issues; Training and development; Policies and practices; and Future challenges.
Includes bibliographical references and indexes.
Description based on print version record.
Keywords: Personnel management -- Psychological aspects; Psychology, Industrial